2016
DOI: 10.1111/aas.12760
|View full text |Cite
|
Sign up to set email alerts
|

Effect of early vs. late tracheostomy on clinical outcomes in critically ill pediatric patients

Abstract: Tracheostomy performed within 14 days after the initiation of MV was associated with reduced duration of MV and length of ICU and hospital stay. Although there was no effect on mortality rate, children may benefit from early tracheostomy without severe complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 27 publications
0
30
0
1
Order By: Relevance
“…The cut-off of 14 days to delineate between early and late tracheostomy was extrapolated from adult studies cited by Holloway et al 8 In their study of 73 pediatric patients, they determined that the total hospital length of stay was 4 weeks shorter in the early tracheostomy group. A similar study of 111 pediatric patients by Lee et al 5 showed a significantly shorter duration of MV, and length of ICU and hospital stay in the early tracheostomy group. In this study, a cut-off of 14 days was also used to classify patients into early and late tracheostomy groups.…”
Section: Resultsmentioning
confidence: 61%
See 3 more Smart Citations
“…The cut-off of 14 days to delineate between early and late tracheostomy was extrapolated from adult studies cited by Holloway et al 8 In their study of 73 pediatric patients, they determined that the total hospital length of stay was 4 weeks shorter in the early tracheostomy group. A similar study of 111 pediatric patients by Lee et al 5 showed a significantly shorter duration of MV, and length of ICU and hospital stay in the early tracheostomy group. In this study, a cut-off of 14 days was also used to classify patients into early and late tracheostomy groups.…”
Section: Resultsmentioning
confidence: 61%
“…10 In contrast, there is still seems to be no definite criteria with regards the timing of tracheostomy in pediatric patients. 4,5 A survey of 28 pediatric intensive care units in the UK showed variation in answers with regards to the duration of invasive ventilation before considering tracheostomy: four units suggested less than 14 days of mechanical ventilation while other units suggested > 14 days or > 28 days with some respondents even considering more than 90 days. 11 Wakeham et al 12 reported a variation of pre-tracheostomy ventilation ranging from 4.3 days to 30.4 days.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(8) 73 çocuk hasta ile yaptıkları çalışmada erken trakeotominin (14 gün) yoğun bakım yatış gününü ve mekanik ventilatörde kalma süresini kısalttığını ancak mortaliteyi etkilemediğini ifade etmiştir. Benzer şekilde Lee ve ark (14). erken trakeotominin (14 gün) mortalite üzerinde etkili olmadığını ancak yoğunbakım yatış süresini ve ventilatör ilişkili pnomoni sıklığını azalttığını belirtmiştir.…”
unclassified